Influence of Plasma Pressure Fluctuation on RF Wave Propagation - 刘智惟 包为民 李小平 刘东林 周辉 (Plasma science & technology, 2016)
Pressure fluctuations in the plasma sheath from spacecraft reentry affect radiofrequency（RF） wave propagation.The influence of these fluctuations on wave propagation and wave properties is studied using methods derived by synthesizing the compressible turbulent flow theory,plasma theory,and electromagnetic wave theory.We study these influences on wave propagation at GPS and Ka frequencies during typical reentry by adopting stratified modeling.We analyzed the variations in reflection and transmission properties induced by pressure fluctuations.Our results show that,at the GPS frequency,if the waves are not totally reflected then the pressure fluctuations can remarkably affect reflection,transmission,and absorption properties.In extreme situations,the fluctuations can even cause blackout.At the Ka frequency,the influences are obvious when the waves are not totally transmitted.The influences are more pronounced at the GPS frequency than at the Ka frequency.This suggests that the latter can mitigate blackout by reducing both the reflection and the absorption of waves,as well as the influences of plasma fluctuations on wave propagation.Given that communication links with the reentry vehicles are susceptible to plasma pressure fluctuations,the influences on link budgets should be taken into consideration.